Peran Metode Pembelajaran Outdoor Learning dalam Meningkatkan Pemahaman Siswa tentang Lingkungan - Liandy, Septian (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2023)
This study aims to analyze the role of the outdoor learning method in improving elementary school students’ understanding of the environment. This research uses a qualitative approach with a library research method. The subjects are elementary school students, and the object is the outdoor learning method and its impact on environmental understanding. Data were collected through literature review from scholarly journals, books, and academic articles published in the last five years. Data were analyzed using content analysis with a descriptive approach. The results indicate that the outdoor learning method effectively enhances students’ understanding of environmental issues by offering direct experiences and contextual learning that connects theory and practice. Furthermore, this method fosters active student engagement, develops social skills, and cultivates environmental awareness from an early age. In conclusion, outdoor learning is a relevant and strategic approach to environmental education at the elementary school level.